Characterization of Bi-doped FAPbI3 perovskite films investigated by X-ray absorption spectroscopy - Tirapat Wechprasit; Atipong Bootchanont; Yingyot Infahsaeng; Poramed Wongjom; Suttipong Wannapaiboon; Anusit Kaewprajak; Pisist Kumnorkaew; Wutthigrai Sailuam; Wittawat Saenrang; Wisanu Pecharapa; Wasan Maiaugree (My University, 2025)
A thorough investigation of perovskite structures formed through doping is essential for advancing the efficiency and stability of perovskite solar cells. In this study, Bi-doped FAPbI3 perovskite films with varying Bi concentrations (0.5-2%) were fabricated using a spin-coating technique on ITO glass substrates. Then the films' phase structure, local structure, and optical characteristics were analyzed. X-ray diffraction (XRD) analysis revealed that the pristine FAPbI3 film exhibited both hexagonal and cubic phases, indicating structural instability. In contrast, Bi-doped FAPbI3 films predominantly displayed a cubic perovskite structure, with a notable reduction in the XRD peak intensity corresponding to the hexagonal phase. UV-Vis spectroscopy showed that the undoped FAPbI3 film had an absorption edge in the visible-near infrared range, while Bi-doping caused a redshift, indicating a reduction in the optical band gap. The calculated results show that optical band gaps decrease with increasing Bi, from a value of 1.49 (pure) to 1.43 (2% Bi) eV. X-ray absorption near edge structure (XANES) analysis confirmed the oxidation states of Pb2+ and Bi3+ ions across all samples, with Bi ions replacing Pb in the local structure. Photoluminescence (PL) measurements revealed an increased PL intensity with 1% Bi doping (7 × 105) compared with pristine FAPbI3 (4.7 × 105), suggesting a reduction in carrier recombination. These findings demonstrate the potential of Bi-doping to stabilize perovskite structures with improved optoelectronic properties.
Keywords: Characterization; X-ray absorption spectroscopy; Perovskite Materials and Applications